Cesarean section rate in Iran, multidimensional approaches for behavioral change of providers: a qualitative study - Rashidian Arash; Mohammad Kazem; Nedjat Saharnaz; Yazdizadeh Bahareh; Changizi Nasrin; Majdzadeh Reza (BMC, 2011)
Abstract Background The cesarean section rate has been steadily rising from 35% in 2000 to 40% in 2005 in Iran. The objective of this study was to identify barriers of reduce the cesarean section rate in Iran, as perceived by obstetricians and midwives as the main behavioral change target groups. Methods A qualitative study with purposive sampling was designed in which data were collected through in-depth interviews and document analyses. Hospitals were selected on the bases of being public and or private and their response to the ministry's C-section reduction interventions. The hospital director, obstetricians and midwives from each hospital were included in the study. The classification of barriers suggested by Grol and Wensing was used for the thematic analysis. Results After 26 in-depth interviews and document analyses, the barriers were identified as: financial, insurance and judicial problems at the economic and political context level; the type and ownership of hospitals, absence of an on call physician, absence of clear job-descriptions for obstetricians and midwives, too many interventions in the delivery process and shortage of human resources and facilities at the organizational context level; distrust and insufficient collaborations between obstetricians and midwives from macro to micro level at the social context level; attitudes toward complications of C-section, reduced capabilities of obstetricians, midwives and residents at the individual professional level; and finally, at the innovation level, vaginal delivery is time consuming, imposes high stress levels and is unpredictable. Conclusion Changing service providers' behavior is not possible through presentation of scientific evidence alone. A multi-level and multidisciplinary approach using behavior change theories is unavoidable. In future studies, the effect of the barriers should be determined to help policy makers recognize the most effective interventional package.